2015
DOI: 10.1186/s12917-015-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Feline calicivirus and other respiratory pathogens in cats with Feline calicivirus-related symptoms and in clinically healthy cats in Switzerland

Abstract: BackgroundCats with feline calicivirus (FCV)-related symptoms are commonly presented to veterinary practitioners. Various clinical manifestations have been attributed to FCV, i.e. upper respiratory tract disease (URTD), oral ulcerations, gingivostomatitis, limping syndrome and virulent systemic disease. Additionally, healthy cats can shed FCV. The aims of this study were 1) to investigate the frequency of FCV in cats with FCV-related symptoms and in healthy cats in Switzerland, 2) to assess risk and protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
4
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 58 publications
9
77
4
11
Order By: Relevance
“…In relation to FCV, it has traditionally been considered as a minor primary conjunctival pathogen (MOCHIZUKI et al, 2000;GERRIETS et al, 2012;BERGER et al, 2015). In the present study it was observed in the same proportion as FHV-1, both in G1 and G2, in different scores, and it is possible that its role has been neglected.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…In relation to FCV, it has traditionally been considered as a minor primary conjunctival pathogen (MOCHIZUKI et al, 2000;GERRIETS et al, 2012;BERGER et al, 2015). In the present study it was observed in the same proportion as FHV-1, both in G1 and G2, in different scores, and it is possible that its role has been neglected.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study it was observed in the same proportion as FHV-1, both in G1 and G2, in different scores, and it is possible that its role has been neglected. This observation underlines the importance of asymptomatic shedders in FCV epidemiology, as previously described by Berger et al (2015). FCV present high genetic variability (COYNE et al, 2006), which can be responsible for the observed diversity on the severity of clinical signs.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations